Pemilihan Merek Beras yang Diminati Konsumen Studi Kasus CV Beras Alami Menggunakan AHP - Agus Salim; Baginda Oloan Lubis (Universitas Bumigora, 2019)
Rice is one of the staple foods of society in general, the need for rice supply is increasing every year. The increasing population in the Jababeka area is a threat to staple food supplies. To determine the selection of Rice Brands, it takes rice criteria in order to determine the best quality of rice, and increase sales. So that it can meet consumer needs for rice. In the selection of rice brands at CV Beras Alami uses a voting system, this is clearly less valid in its election because it is subjective. Analytical Hierarchy Process (AHP) method is used as a method for decision making, as a solution in selecting rice brands in CV Beras Alami. The Expert Choice application is used as a support system to facilitate the selection of rice brands that are in demand by consumers. The results can be known during the 2018 period that rice is widely consumed is Garuda Utama.